Study on the Influence of Excavation Unloading on Pile Depth in Sandy Soil. (28th July 2022) - Zhanjun, Huang; Yi, Zou; Haibin, Ding; Xinhuan, Liang; Bitang, Zhu; Yalong, Jiang
Abstract : With the development of urban construction, uplift pile has been widely used in underground structure bearing buoyancy. The pile is buried deep underground, and the foundation pit is excavated on the pile foundation, the stress redistribution of the soil after the foundation pit excavation will reduce the lateral stress of the pile at the bottom of the pit, resulting in the reduction of friction resistance, but this effect is limited to a certain depth at the bottom of the foundation pit. Referring to the unloading influence depth corresponding to the vertical unloading coefficient in the spring back calculation of foundation pit and introducing the unloading influence depth corresponding to the horizontal unloading coefficient, it is deduced that the relationship between the horizontal unloading coefficient and the vertical unloading coefficient is based on the friction angle. Based on the bearing capacity control and numerical simulation, it is determined that the corresponding depth when the horizontal unloading coefficient is 0.95 is the unloading influence depth. The depth to width ratio of excavation has a great influence on unloading influence depth, and the internal friction angle of soil has little influence on unloading influence depth, while the influences of pile diameter and pile-soil friction coefficient can be ignored. The formula of unloading influence depth is derived in this paper. Comparing the unloading influence depth of sand and soft soil, the unloading influence depth of sand is greater than that of soft soil.